KEBERADAAN KETERANGAN HASIL DARI LIE DETECTOR SEBAGAI ALAT BUKTI DALAM PEMERIKSAAN TINDAK PIDANA PEMBUNUHAN BERENCANA ALM. NOFRIANSYAH YOSUA HUTABARAT (STUDI PUTUSAN NO. 796/PID.B/2022/PN JKT.SEL): The Existence Of Information Result From The Lie Detector As Evidence In The Examination Of The Crime Of Premeditated Murder Of The Late Nofriansyah Yosua Hutabarat (Study Of Decision No. 796/Pid.B/2022/Pn Jkt.Sel)) - Allesandro Nesta Mahat; Abdul Ficar Hadjar (AMICUS CURIAE, 2025)
Legal ambiguity can be caused by the limitations and breadth of evidence that is not covered by Law Number 8 of 1981 (KUHAP). The use of a lie detector as an investigator's instrument can assist the investigator in guiding further investigation or determining the direction of the investigation. The identification of the problem that the author discusses in this thesis is whether the results of the lie detector are in accordance with the Criminal Procedure Code and what are the legal consequences of the lie detector results. The method of writing that the author uses is normative legal, the nature of descriptive writing, the type of data using secondary data, and the conclusion is drawn by deductive logic. There are different interpretations regarding the use of Lie Detector in Decision No. 796/Pid.B/PN.Jkt.Sel in proving criminal cases. Some parties argue that Lie Detector is evidence, while others argue that Lie Detector is evidence. However, from the perspective of legal experts, Lie Detector is only considered as an instrument or tool to assist investigators in uncovering criminal acts and providing more detailed clarification. The use of Lie Detector is still a controversy.